2014
DOI: 10.3892/ol.2014.2231
|View full text |Cite
|
Sign up to set email alerts
|

Progress of cancer research on astrocyte elevated gene-1/Metadherin (Review)

Abstract: Tumor development is initiated by an accumulation of numerous genetic and epigenetic alterations that promote tumor initiation, invasion and metastasis. Astrocyte elevated gene-1 [AEG-1; also known as Metadherin (MTDH) and Lysine-rich CEACAM1 co-isolated (LYRIC)] has emerged in recent years as a potentially crucial mediator of tumor malignancy, and a key converging point of a complex network of oncogenic signaling pathways. AEG-1/MTDH has a multifunctional role in tumor development that has been found to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 97 publications
(175 reference statements)
1
34
0
Order By: Relevance
“…23,24 As a target of Ras, MTDH activates multiple oncogenic signaling pathways including phosphoinositide-3 kinase (PI3K)-Akt, mitogen-activated protein kinase (MAPK), Wnt, and NF-kB involved in regulation of proliferation, invasion, chemoresistance, angiogenesis, and metastasis. [25][26][27][28] In particular, MTDH showed higher expression, compared with that in normal brain tissues, in tumors of the CNS, such as neuroblastoma, glioblastoma multiforme, and oligodendroglioma.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 As a target of Ras, MTDH activates multiple oncogenic signaling pathways including phosphoinositide-3 kinase (PI3K)-Akt, mitogen-activated protein kinase (MAPK), Wnt, and NF-kB involved in regulation of proliferation, invasion, chemoresistance, angiogenesis, and metastasis. [25][26][27][28] In particular, MTDH showed higher expression, compared with that in normal brain tissues, in tumors of the CNS, such as neuroblastoma, glioblastoma multiforme, and oligodendroglioma.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] The expression level of AEG-1 is aberrantly high in melanoma. 21,22 Clinical studies showed that elevated expression of AEG-1 was associated with tumour progression and poor prognosis of melanoma. 22However, the exact role of AEG-1 in melanoma cells is not clear.…”
mentioning
confidence: 99%
“…PI3K/Akt signaling primarily exerts anti-apoptotic effects by affecting multiple downstream effector molecules (34). Knockout of PI3K, Akt and associated genes by genetic intervention, or inhibition by small molecule drugs, which blocks the activation of downstream anti-apoptotic effector molecules and promotes apoptosis, has become a key focus of research on cancer treatment (35). The results of the present study suggested that psoralidin was able to reduce the protein expression levels of PI3K and Akt in Eca9706 cells; however, upregulation of PI3K protein expression reduced the viability of Eca9706 cells.…”
Section: Discussionmentioning
confidence: 99%